The generality of word-association hierarchies : I. Production and recall of association responses - Made-van Bekkum, Ida J. van der; Prevo-Molenaar, Jitske (Elsevier, 1968)
Ss responded to a stimuluslist in a free word association session (AS) and tried to recall their response to each stimulus in a recall session (RS). There was a significant positive correlation between commonality score (Co) in AS and number of correct reproductions in RS. All Ss tended to gain in Co, but LC (i.e., Ss of low Co in AS) more than HC (i.e., Ss of high Co in AS). Marbe's law applied both to the group of mean scores per S per session and (more or less) to the data of each S separately (no difference between HC and LC) in one or both sessions. Apparently the responses of LC really were, even for themselves, improbable ones likely to be forgotten and to be substituted by more probable ones (in terms of group norms).
Keywords: Sociale Wetenschappen